Money transmission mechanisms and output in Trinidad and Tobago - Watson, Patrick ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Evaluates the impact of a monetary shock on monetary, and, more importantly, real variables (like prices, employment, income and so on}.